EARNINGS MANAGEMENT THROUGH THE LENS OF DEFERRED TAX AND TAX PLANNING: AN EMPIRICAL STUDY - Agustine Dwianika; Sendi Tri Andika; Selvia Ely Zanna (ZILLZELL MEDIA PRIMA, 2025)
This research aims to analyze the influence of deferred tax expense and tax planning on earnings management in healthcare sector companies listed on the Indonesia Stock Exchange during the period 2018–2024. The study employs panel data regression to examine the relationships between the variables. The research findings indicate that dividend policy has a significant positive effect on earnings management, while both deferred tax expense and tax planning also show a significant positive relationship with earnings management. These results suggest that companies may use tax-related strategies, including the deferral of tax obligations and planning of tax payments, as tools to manage reported earnings. This study contributes to the growing literature by providing insights for practitioners, regulators, and academics into how tax-related components and dividend policy can influence earnings management behavior in the healthcare industry. The practical implication of this research emphasizes the need for careful integration of tax considerations in dividend policy decisions to reduce the risk of opportunistic earnings management.